Gabor Kemenesi - Jakimovski, Dejan; Pavle Banović; Spasovska, Katerina; Goran Rangelov; Cvetanovska, Marija; Fadil Cana; Verica Simin; Ivana Bogdan; Dragana Mijatović; Cvetkovikj, Aleksandar; Dјadјovski, Igor; Iva Christova; et al. (Eurosurveillance, 2025)
Background Crimean–Congo haemorrhagic fever (CCHF) is a severe illness characterised by fever, bleeding and high case-fatality rates. The disease is caused by CCHF virus (CCHFV), transmitted by ticks and infectious body fluids and tissues. Aim After CCHF was diagnosed in three persons in 2023, we aimed to investigate the presence of antibodies against CCHFV in healthcare workers (HCW), sheep and goats, and of CCHFV in ticks, in an area in North Macedonia and characterise virus strains. Methods In 2023, we collected blood samples from HCWs involved in treating CCHF patients and sera and ticks from sheep and goats in the village in North Macedonia where the index case resided. The blood samples were analysed by ELISA. Ticks were tested for presence of CCHFV, and the virus from a CCHF case was sequenced. Results Samples from four of 52 HCWs and 10 of 17 small ruminants had antibodies against CCHFV. The virus was not detected from any of the 24 Rhipicephalus bursa ticks. The virus strain from the index case clustered with regional strains within the Europe-1 lineage (genotype V) group and was closest to strains from Kosovo‡. Conclusion This report shows CCHFV is endemic in North Macedonia. Raising awareness of the risk factors and educating people about the measures they can take to reduce exposure to the virus is important. Healthcare workers need to be aware of the disease. Early detection, robust diagnostic methods, surveillance and collaborative efforts are necessary to prevent and control CCHF in the affected regions.